2014
DOI: 10.4103/1817-1737.140135
|View full text |Cite
|
Sign up to set email alerts
|

Value of neutrophil/lymphocyte ratio in the differential diagnosis of sarcoidosis and tuberculosis

Abstract: INTRODUCTION:The differential diagnosis of sarcoidosis creates a challange due to tuberculosis also having lung and lymph node involvement. Because both diseases show granulomatous inflammation, it may not be possible to distinguish tuberculosis and sarcoidosis in pathological specimens. As a result of the complexity in the differential diagnosis of sarcoidosis and tuberculosis, new markers for differentiation are being investigated.OBJECTIVE:The aim of our study is to investigate the value of neutrophil/lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 18 publications
5
64
1
2
Order By: Relevance
“…It can be easily calculated from a routine complete blood count and is determined by dividing the absolute neutrophil count by the number of lymphocytes. In a Turkish study that compared sarcoidosis and control groups, neutrophil count, NLR and CRP were significantly higher, and lymphocytes were significantly lower in the sarcoidosis group [20]. Additionally, Dirican et al [21] concluded that a higher NLR (≥2) was detected in patients with sarcoidosis and that this was more frequent in patients with extrapulmonary involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be easily calculated from a routine complete blood count and is determined by dividing the absolute neutrophil count by the number of lymphocytes. In a Turkish study that compared sarcoidosis and control groups, neutrophil count, NLR and CRP were significantly higher, and lymphocytes were significantly lower in the sarcoidosis group [20]. Additionally, Dirican et al [21] concluded that a higher NLR (≥2) was detected in patients with sarcoidosis and that this was more frequent in patients with extrapulmonary involvement.…”
Section: Discussionmentioning
confidence: 99%
“…The NLR has emerged as a new marker of inflammation [20,21]. It can be easily calculated from a routine complete blood count and is determined by dividing the absolute neutrophil count by the number of lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The NLR ratio was calculated by dividing the absolute neutrophil count by the abolute lymphocyte count (12,13).…”
Section: Datamentioning
confidence: 99%
“…The signifi cance of NLR in the diagnosis, follow-up and activity in sarcoidosis is not precisely known. However, there is a limited number of studies that recommend the utilization of Neutrophil/ Lymphocyte ratio in the differential diagnosis and determination of the prognosis (12,13).…”
Section: Introductıonmentioning
confidence: 99%
“…Some recent studies have shown that NLR and PLR have a diagnostic value in certain pathologies characterised by systemic or local inflammatory response, such as diabetes mellitus, coronary artery disease, ulcerative colitis, sarcoidosis, tuberculosis and inflammatory arthritis (5)(6)(7)(8)(9)(10) .…”
Section: Introductionmentioning
confidence: 99%